Development of benzochalcone derivatives as selective CYP1B1 inhibitors and anticancer agents. Issue 9 (23rd July 2019) - Dong, Jinyun; Huang, Guang; Zhang, Qijing; Wang, Zengtao; Cui, Jiahua; Wu, Yan; Meng, Qingqing; Li, Shaoshun
Abstract : A series of benzochalcone derivatives have been synthesized and evaluated for CYP1 inhibitory activity and cytotoxic properties against wild type cell lines (MCF-7 and MDA-MB-231) and drug resistant cell lines (LCC6/P-gp and MCF-7/1B1). Abstract : A series of benzochalcone derivatives have been synthesized and evaluated for CYP1 inhibitory activity and cytotoxic properties against wild type cell lines (MCF-7 and MDA-MB-231) and drug resistant cell lines (LCC6/P-gp and MCF-7/1B1). All of these compounds were found to have selective inhibition towards CYP1B1 and the most potent two possessed single-digit nanomolar CYP1B1 potency. In addition, some of them showed promising cytotoxic activities not only against wild type cells, but also against drug resistant cells at low micromolar concentrations. More importantly, these multi-functional compounds may surmount drug–drug interactions that frequently occur during the combination of CYP1B1/P-gp inhibitors and anticancer drugs to overcome drug resistance. This study may provide a good starting point for the further development of more potent multi-functional agents with CYP1B1 inhibitory activity and cytotoxic potency in cancer prevention and treatment.